Photostimulated Tension Effects in TlInSe2 Crystals - S. H. Umarov; N. Z. Gasanov; R. R.Khamroev (Zien Journals, 2022)
The paper presents the results of a study of photostimulated strain effects in TlInSe2 single crystals. It was found that the absolute value of the photocurrent in positively (compression) deformed samples increases, and in negatively (stretching) deformed samples – decreases in comparison with the undeformed sample. At the same time, the maximum of the photocurrent does not change, which indicates that the width of the direct transitions of TlInSe2 crystals remains unchanged under various types of deformation
Keywords: photostimulated strain effects; the absolute value of the photocurrent; positively deformed; negatively deformed